1
$\begingroup$

I am trying to derive the formula for the variance of a geometric distribution and am stuck at the following problem:

I need to find the sum to infinity for the following series:

$1+3(1-p)+5(1-p)^2+7(1-p)^3+\dots$ where $p$ where $p$ is a constant $0<p<1$

The series looks like the sum of the odd numbers and the sum of a geometric series (with common ration $(1-p)$) combined.

I don't know how to deal with such series. Please tell me how to solve this.

$\endgroup$
4
$\begingroup$

Write $q = \sqrt{1-p}$. Then your series becomes

$$1\cdot q^0 + 3\cdot q^2 + 5\cdot q^4 + 7\cdot q^6 +\dotsb = \sum_{k=0}^\infty (2k+1)\cdot q^{2k}.$$

The latter is easily recognised as

$$\frac{d}{dq} \sum_{k=0}^\infty q^{2k+1} = \frac{d}{dq} q\sum_{k=0}^\infty (q^2)^k = \frac{d}{dq} \frac{q}{1-q^2} = \frac{(1-q^2) -(-2q)q}{(1-q^2)^2} = \frac{1+q^2}{(1-q^2)^2}.$$

Now insert $q^2 = 1-p$ to obtain

$$\frac{2-p}{p^2}.$$

$\endgroup$
1
$\begingroup$

Sketch:

Let $T=\sum_{k=0}^\infty (2k+1)q^k$ be the series you want to evaluate ($q=1-p$) and $S=\sum_{k=0}^\infty 2kq^k$. We have $$ T=S+\sum_{k=0}^\infty q^k, $$ where we can calculate the second series with the formula for geometric series. So you can figure out $T$ by calculating $S$. Now $$ S=2\sum_{k=0}^\infty kq^k=2q\frac{d(\sum_{k=0}^\infty q^k)}{dq} $$ Again, you can evaluate the last bit by using the formula for geometric series and differentiating the result.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.